Effect of Gas Flowrate on Nucleation Mechanism of MWCNTs for a Compound Catalyst. (14th November 2017) - Shukrullah, S.; Mohamed, N. M.; Khan, Y.; Naz, M. Y.; Ghaffar, A.; Ahmad, I.
Abstract : Activation of the catalyst particles during a CVD process can be anticipated from the carbon feeding rate. In this study, Fe2 O3 /Al2 O3 catalyst was synthesized with uniformly dispersed iron over alumina support for onward production of multiwalled carbon nanotubes (MWCNTs) in a fluidized bed chemical CVD reactor. The effect of the ethylene flowrate on catalytic activity of the compound catalyst and morphology of the as-grown MWCNTs was also investigated in this study. The dispersed active phases of the catalyst and optimized gas flowrate helped in improving the tube morphology and prevented the aggregation of the as-grown MWCNTs. The flowrates, below 100 sccm, did not provide sufficient reactants to interact with the catalyst for production of defect-free CNT structures. Above 100 sccm, concentration of the carbon precursor did not show notable influence on decomposition rate of the gas molecules. The most promising results on growth and structural properties of MWCNTs were gained at ethylene flowrate of 100 sccm. At this flowrate, the ratio of G and D intensity peaks (I G / I D ) was deliberated about 1.40, which indicates the growth of graphitic structures of MWCNTs.